A Descriptive Study into Implementation Challenges and Promotion Measures for E-commerce during COVID-19 Period - Harish, S; Renugadevi, S (Journal of Advanced Research in Service Management, 2022)
Due to the rapid development on technology and science, the emergence of implementing new methods and forms of economic activities arise. E-commerce in India faces some obstacles to prosper and grow including regulations, infrastructure and the business environment. It is expected e-commerce market in India of the total business transactions over the Internet in 2015 to grow by 8%. Majority (37%) of the respondents agreed consumer’s awareness is low. 41% of the respondents recommended promotion of internet as the best strategy. How to cite this article: Renugadevi S, Harish S. A Descriptive Study into Implementation Challenges and Promotion Measures for E-commerce during COVID-19 Period. J Adv Res Servi Mgmt 2021; 4(2): 1-4.